Syntax of the Guided Inquiry Learning Model Based on Local Wisdom of Baduy's Society Towards Scientific Literacy on Environmental Conservation Theme - Lukman Nulhakim; Liska Berlian; Aditya Rakhmawan; Asep Saefullah; Rt. Bai Rohimah; Bayu Fadhliana Firdaus; Amin Hasan; R. Ahmad Zaky El Islami; Indah Juwita Sari (Gagasan Pendidikan Indonesia, 2022)
This research aimed to develop the syntax of guided inquiry learning based on the local wisdom of the Baduy’s society, which is oriented towards student scientific literacy on environmental conservation. The method used is mixed-method with a sample in this study were 15 students. The syntax of guided inquiry learning in the implementation consists of six stages; orientation, presenting the problem, hypothesis submission, data collection, hypothesis testing, and conclusion formulation. In the orientation stage, students describe the context that comes from the local wisdom of the Baduy’s society. In presenting the problem, students asked questions about the science content related to the context of the local wisdom of the Baduy’s society, which was described earlier. In the hypothesis submission stage, the teacher asks students to submit hypotheses related to the previous questions. In the data collection stage, the teacher provides questions in the form of science content, scientific processes, and scientific attitudes to be answered by students that can be used to test hypotheses. In the hypothesis testing stage, students use the data that has been collected. In the conclusion formulation stage, students conclude the results of hypothesis testing using the data that has been collected. Implementing guided inquiry learning based on the local wisdom of the Baduy’s society can improve scientific literacy (N-Gain = 0.064). So, we can use guided inquiry learning based on the local wisdom of the Baduy’s society, which is oriented towards student scientific literacy on environmental conservation using six stages.